2020
DOI: 10.3389/fnbeh.2020.00095
|View full text |Cite
|
Sign up to set email alerts
|

Dissociating Cognitive Processes During Ambiguous Information Processing in Perceptual Decision-Making

Abstract: Decision-making requires the accumulation of sensory evidence. However, in everyday life, sensory information is often ambiguous and contains decision-irrelevant features. This means that the brain must disambiguate sensory input and extract decision-relevant features. Sensory information processing and decision-making represent two subsequent stages of the perceptual decision-making process. While sensory processing relies on occipito-parietal neuronal activity during the earlier time window, decision-making … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 37 publications
3
27
0
Order By: Relevance
“…On the one hand, this set could be separated into subsets of left-oriented (LO) a = {0.15, 0.25, 0.4, 0.45} and right-oriented (RO) cubes a = {0.55, 0.6, 0.75, 0.85}. On the other hand, in accordance with our previous study 14 , this set could be also divided into low-ambiguous (LA) images a = {0.15, 0.25, 0.75, 0.85}, which are easily interpreted by an observer, and high-ambiguous (HA) images a = {0.40, 0.45, 0.55, 0.60}, whose interpretations requires more effort. We also supposed that HA processing engages more top-down control.…”
Section: Visual Stimulisupporting
confidence: 87%
See 2 more Smart Citations
“…On the one hand, this set could be separated into subsets of left-oriented (LO) a = {0.15, 0.25, 0.4, 0.45} and right-oriented (RO) cubes a = {0.55, 0.6, 0.75, 0.85}. On the other hand, in accordance with our previous study 14 , this set could be also divided into low-ambiguous (LA) images a = {0.15, 0.25, 0.75, 0.85}, which are easily interpreted by an observer, and high-ambiguous (HA) images a = {0.40, 0.45, 0.55, 0.60}, whose interpretations requires more effort. We also supposed that HA processing engages more top-down control.…”
Section: Visual Stimulisupporting
confidence: 87%
“…Considering response times (RT), we found that high ambiguity increases RT, as reported in our earlier works on the Necker cube perception 14,15 . We also observed that for low ambiguity, subjects responded faster to the left-oriented than right-oriented stimuli.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…We revealed that the subjects responded to LA stimuli faster and more correctly than to HA stimuli that coincides with our previous findings 12,26 . In the latter case, they deal with ambiguous sensory information and may increasingly rely on the top-down processes, such as expectations and memory, to make a correct decision 9,13 . When processing LA stimuli, subjects responded quicker to the left-oriented stimuli than to the right-oriented ones.…”
Section: Discussionmentioning
confidence: 99%
“…* email: maximenkovl@gmail.com Experimental procedure. We chose an ambiguous drawing of a Necker cube as a bistable visual stimulus [11][12][13] . The ambiguity, as well as the orientation of the cube's image, was determined by the balance between the brightness of the inner edges forming a left-lower ( b l = 1 − a ) and right-upper ( b r = a ) squares, where a ∈ [0, 1] was a normalized edge's luminance in a gray-scale palette.…”
Section: Openmentioning
confidence: 99%